2021
DOI: 10.3389/fgene.2021.681768
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Septoria Nodorum Blotch (SNB) Resistance in Glumes of Wheat (Triticum aestivum L.) and the Genetic Relationship With Foliar Disease Response

Abstract: Septoria nodorum blotch (SNB) is a necrotrophic disease of wheat prominent in some parts of the world, including Western Australia (WA) causing significant losses in grain yield. The genetic mechanisms for resistance are complex involving multiple quantitative trait loci. In order to decipher comparable or independent regulation, this study identified the genetic control for glume compared to foliar resistance across four environments in WA against 37 different isolates. High proportion of the phenotypic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…were reported by four other groups [14,16,52,53]. They found significant, moderately negative correlation of heading date and plant height with leaf and glume disease severity within and across environments.…”
Section: Plos Onementioning
confidence: 72%
“…were reported by four other groups [14,16,52,53]. They found significant, moderately negative correlation of heading date and plant height with leaf and glume disease severity within and across environments.…”
Section: Plos Onementioning
confidence: 72%
“…In contrast, high phenotypic correlation but the lack of common QTL detected between field and GH experiments in 2019 indicated genetic variation within the population contributed to cumulative influence of different loci, such as those with possible small effects but below statistical power for detection in the GWAS analysis. The cumulative effect of environment-specific QTL of small and large effects and associated gene variants contributing to high phenotypic correlation was recently reported for fungal disease response in wheat (Joukhadar et al, 2020;Francki et al, 2021;Li et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…In addition to resistance against biotrophic fungi, such as rust and powdery mildew, studies have reported the involvement of APR genes in resistance against hemibiotrophic and necrotrophic diseases, such as tan spot [ 27 ], Septoria nodorum blotch [ 28 ] and Fusarium head blight/crown rot [ 29 ] of wheat. Outside the cereals, APR genes are also known globally for their involvement in resistance against important diseases of other crops, such as maize northern leaf spot [ 30 ], canola blackleg [ 31 ], Brassica downy mildew [ 32 ], chickpea Fusarium wilt and Ascochyta blight [ 33 ], and soybean powdery mildew [ 34 ].…”
Section: Apr: the Wheat-rust Pathosystemmentioning
confidence: 99%